Multicenter study on the genetics of glomerular diseases among southeast and south Asians: Deciphering Diversities ‐ Renal Asian Genetics Network (DRAGoN). Issue 5 (1st February 2022) - Lu, Liangjian; Yap, Yok‐Chin; Nguyen, Duc Quang; Chan, Yiong‐Huak; Ng, Jun‐Li; Zhang, Yao‐Chun; Chan, Chang‐Yien; Than, Mya; Liu, Isaac Desheng; Asim, Sadaf; Moorani, Khemchand; Naeem, Bilquis; et al.
Abstract: Multinational studies have reported monogenic etiologies in 25%–30% of children with steroid‐resistant nephrotic syndrome. Such large studies are lacking in Asia. We established Deciphering Diversities: Renal Asian Genetics Network (DRAGoN) and aimed to describe the genetic and clinical spectrums in Asians. We prospectively studied a cohort of 183 probands with suspected genetic glomerulopathies from South and Southeast Asia, of whom 17% had positive family history. Using multi‐gene panel sequencing, we detected pathogenic variants in 26 (14%) probands, of whom one‐third had COL4A4 or COL4A5 variants ( n  = 9, 5%). Of those with COL4A5 defects, only 25% had features suggestive of Alport syndrome. Besides traditional predictors for genetic disease (positive family history and extrarenal malformations), we identified novel predictors, namely older age (6.2 vs. 2.4 years; p  = 0.001), hematuria (OR 5.6; 95% CI 2.1–14.8; p  < 0.001), and proteinuria in the absence of nephrotic syndrome (OR 4.6; 95% CI 1.8–11.8; p  = 0.001) at first manifestation. Among patients who first presented with proteinuria without nephrotic syndrome, the genetic diagnostic rates were >60% when a second risk factor (positive family history or extrarenal manifestation) co‐existed. The genetic spectrum of glomerulopathies appears different in Asia. Collagen IV genes may be included in sequencing panels even when suggestive clinical features are absent. Abstract :